Influence of Independent Commissioners and Audit Committee on the Performance of State-Owned Enterprises in Indonesia Moderated by Dual Positions of the Commissioner - Dwi Setyo Aji; Lenggogeni Lenggogeni (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of the Independent Board of Commissioners and the Audit Committee on the Performance of State-Owned Enterprises in Indonesia. This study also examines the effect of concurrent positions of commissioners as a moderating variable which is thought to have an effect on the performance of state-owned enterprises. The dual position of the Commissioner is suspected to affect the role of the independent variable on the dependent variable. The Financial Performance of State-Owned Enterprises is proxied using Return on Assets (RoA), the Independent Board of Commissioners uses a proxy for the number of independent commissioners in the company, and the Audit Committee uses a proxy for the number of audit committee members in a company. The sample of this research is 20 State-Owned Enterprises that are listed on the Indonesia Stock Exchange (IDX) during the period 2016 to 2019, so that a total of 80 research samples are obtained. The analytical method used to test the hypothesis in this study is moderated regression analysis (MRA) and uses statistical tools in the form of the Eviews version 12 application. The results of this study indicate that the independent board of commissioners variable has no effect on the performance of State-Owned Enterprises, the Audit Committee variable has an effect on the Performance of State-Owned Enterprises, and Concurrent Positions of Commissioners have no effect and do not moderate the influence of independent commissioners and audit committees on the financial performance of State-Owned Enterprises.